Smart Grid: Assessment of the past and present in developed and developing countries. (December 2017) - Ponce-Jara, M.A.; Ruiz, E.; Gil, R.; Sancristóbal, E.; Pérez-Molina, C.; Castro, M.
Abstract: The modern struggle to generate electricity reducing our dependence on fossil fuels and decreasing greenhouse gas emissions has found an ally in Smart Grid technology. This new trend involves a renewed perspective on how to generate, transmit, distribute and manage electricity networks, which not only helps to reduce power demand and cost, but can also improve efficiency, reliability, quality and security. This paper aims to study comprehensively the Smart Grid power system by comparing experiences and success stories from around the world. Developed countries, like the United States and those in the European Union, and developing countries, like India and Brazil, have been taken as examples of the current development and state of the Smart Grid concept. Europe and the U.S. lead the development of Smart Grids systems, while Brazil and India strongly depend on foreign technology and investment for their development in their countries. Climate change represents an extra challenge for developing countries, in addition to other issues related to economic and social advancement. Nevertheless, Smart Grids offer an array of possibilities and opportunities that work towards climate change international goals. However, state motivations and national energy resources limit the advancement of Smart Grids on this matter. Highlights: Power grids in developing countries were strongly influenced by colonialism and political instability. The E.U. and U.S. are focused on strengthening their interconnections when deploying Smart Grids. Brazil and India are investing in reducing energy losses and power theft. In all four scenarios governments have developed similar processes to implement policies toward Smart Grids. Energy Internet is presented as the natural evolution of Smart Grid and IoT.